2015
DOI: 10.1016/j.atmosenv.2015.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of global wildfire occurrences to various factors in the context of global change

Abstract: h i g h l i g h t sWe investigate the potential impacts of global change on wildfire frequencies.We account for changing fire meteorology, lightning, population, land use/land cover. Fire frequencies are projected to increase by~27% due to 2000e2050 global change. Fire meteorology change is the most important factor, followed by land cover. a b s t r a c tThe occurrence of wildfires is very sensitive to fire meteorology, vegetation type and coverage. We investigate the potential impacts of global change (inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 23 publications
0
32
1
Order By: Relevance
“…This result contrasts with other studies that found stronger influences of climate than LULC on fire occurrence when using remote sensors [17,22,50]. An open question remains how different resolution fire data are explained by variables operating at different scales.…”
Section: Forest Ecology and Conservationcontrasting
confidence: 55%
See 1 more Smart Citation
“…This result contrasts with other studies that found stronger influences of climate than LULC on fire occurrence when using remote sensors [17,22,50]. An open question remains how different resolution fire data are explained by variables operating at different scales.…”
Section: Forest Ecology and Conservationcontrasting
confidence: 55%
“…Fire occurrence and spread is also controlled by local factors such as ignition source, topography, local weather patterns, variations in fuels type and condition, and management actions [6,7,9,[11][12][13][14][15]. Because of the complex interplay among drivers of wildfires, predicting fire occurrence in the context of global change is a challenge [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Fire events are becoming more frequent in occurrence, and larger in terms of areal coverage [1]. Analyses of charcoal records in sediments and isotopic records in ice cores have indicated lower biomass burning in present times than any time in the previous 2000 years [2,3], but Huang et al [1] and North et al [4] reported an increase in the occurrence of wildfires. Data from Europe, Australia, and New Zealand also show a decline in the occurrence of fire events but similar data sets from South East Asia, the Middle East and North America show an increase [5].…”
Section: Introductionmentioning
confidence: 99%
“…Results from studies carried out around the globe indicate that spatially, fire incidents occur in every continent except Antarctica whereas temporal occurrence is related to climatic changes [6]. According to Huang et al [1], lightning, climate change and precipitation will account for 3.6%, 19%, and 36.7% increase in the occurrence of wildfires respectively by the year 2050. Lightning, volcanic eruptions, and sparks from rock falls are natural occurrences which have been cited as being responsible for wildfires.…”
Section: Introductionmentioning
confidence: 99%
“…About 9 to 10 lightning-related deaths and 19 to 164 injuries occur each year in Canada, costing between $3.6 and $79.2 million [ 1 ]. The lightning activity is a major natural ignition source for global wildfires and was parameterized as a driving factor to generate simulated wildfire model [ 2 , 3 ]. There is an average of 816 fires ignited by lightning each year.…”
Section: Introductionmentioning
confidence: 99%